Noninvasive Mechanical Joint Loading as an Alternative Model for Osteoarthritic Pain. Issue 7 (17th May 2019) - ter Heegde, Freija; Luiz, Ana P.; Santana‐Varela, Sonia; Chessell, Iain P.; Welsh, Fraser; Wood, John N.; Chenu, Chantal
Abstract : Objective: Mechanisms responsible for osteoarthritic (OA) pain remain poorly understood, and current analgesic therapies are often insufficient. This study was undertaken to characterize and pharmacologically test the pain phenotype of a noninvasive mechanical joint loading model of OA, thus providing an alternative murine model for OA pain. Methods: The right knees of 12‐week‐old male C57BL/6 mice were loaded at 9N or 11N (40 cycles, 3 times per week for 2 weeks). Behavioral measurements of limb disuse and mechanical and thermal hypersensitivity were acquired before mechanical joint loading and monitored for 6 weeks postloading. The severity of articular cartilage lesions was determined postmortem with the Osteoarthritis Research Society International scoring system. To assess efficacy of various treatments for pain, 9N‐loaded mice were treated for 4 weeks with diclofenac (10 mg/kg), gabapentin (100 mg/kg), or anti–nerve growth factor (anti‐NGF) (3 mg/kg). Results: Mechanical hypersensitivity and weight bearing worsened significantly in 9N‐loaded mice (n = 8) and 11N‐loaded mice (n = 8) 2 weeks postloading, compared to baseline values and nonloaded controls. Maximum OA scores of ipsilateral knees confirmed increased cartilage lesions in 9N‐loaded mice (mean ± SEM 2.8 ± 0.2; P < 0.001) and 11N‐loaded mice (5.3 ± 0.3; P < 0.001), compared to nonloaded controls (1.0 ± 0.0). Gabapentin and diclofenac restored pain behaviors to baseline values after 2 weeks of daily treatment, and gabapentin was more effective than diclofenac. A single injection of anti‐NGF alleviated nociception 2 days after treatment and remained effective for 2 weeks, with a second dose inducing stronger and more prolonged analgesia. Conclusion: Our findings show that mechanical joint loading induces OA lesions in mice and a robust pain phenotype that can be reversed using analgesics known to alleviate OA pain in patients. This establishes the use of mechanical joint loading as an alternative model for the study of OA pain.